"Need for Speed" Documentary of the Postdoc Working Group "Rethinking Accelerated Learning" (Postdoc Working Group Accelerated Learning, 2025)
The Postdoc Working Group's workshop in February was accompanied by a film screening of documentary "Need for Speed: African and Asian Students on Accelerated Learning at University of Bayreuth". The film explores the experiences of African and Asian students navigating accelerated learning programmes at University of Bayreuth, highlighting both challenges and opportunities. The film examines how accelerated learning impacts students' academic adaptation, career preparedness, and cultural integration. The screening provided a platform for discussions on inclusivity and the future of higher education in a rapidly evolvling global landscape.